Si/SiGe Heterointerfaces in One-, Two-, and Three-Dimensional Nanostructures: Their Impact on SiGe Light Emission - Lockwood, David J.; Wu, Xiaohua; Baribeau, Jean-Marc; Mala, Selina A.; Wang, Xiaolu; Tsybeskov, Leonid (Frontiers in Materials, 2016)
Fast optical interconnects together with an associated light emitter that are both compatible with conventional Si-based complementary metal-oxide- semiconductor (CMOS) integrated circuit technology is an unavoidable requirement for the next-generation microprocessors and computers. Self-assembled Si/Si1-xGex nanostructures, which can emit light at wavelengths within the important optical communication wavelength range of 1.3 – 1.55 μm, are already compatible with standard CMOS practices. However, the expected long carrier radiative lifetimes observed to date in Si and Si/Si1-xGex nanostructures have prevented the attainment of efficient light-emitting devices including the desired lasers. Thus, the engineering of Si/Si1-xGex heterostructures having a controlled composition and sharp interfaces is crucial for producing the requisite fast and efficient photoluminescence (PL) at energies in the range 0.8-0.9 eV. In this paper we assess how the nature of the interfaces between SiGe nanostructures and Si in heterostructures strongly affects carrier mobility and recombination for physical confinement in three dimensions (corresponding to the case of quantum dots), two dimensions (corresponding to quantum wires), and one dimension (corresponding to quantum wells). The interface sharpness is influenced by many factors such as growth conditions, strain, and thermal processing, which in practice can make it difficult to attain the ideal structures required. This is certainly the case for nanostructure confinement in one dimension. However, we demonstrate that axial Si/Ge nanowire (NW) heterojunctions (HJs) with a Si/Ge NW diameter in the range 50 – 120 nm produce a clear PL signal associated with band-to-band electron-hole recombination at the NW HJ that is attributed to a specific interfacial SiGe alloy composition. For three-dimensional confinement, the experiments outlined here show that two quite different Si1-xGex nanostructures incorporated into a Si0.6Ge0.4 wavy superlattice structure display PL of high intensity while exhibiting a characteristic decay time that is up to 1000 times shorter than that found in conventional Si/SiGe nanostructures. The non-exponential PL decay found experimentally in Si/SiGe nanostructures can be interpreted as resulting from variations in the separation distance between electrons and holes at the Si/SiGe heterointerface. The results demonstrate that a sharp Si/SiGe heterointerface acts to reduce the carrier radiative recombination lifetime and increase the PL quantum